Ropinirole and Pramipexole Promote Structural Plasticity in Human iPSC-Derived Dopaminergic Neurons via BDNF and mTOR Signaling. (4th February 2018) - Collo, Ginetta; Cavalleri, Laura; Bono, Federica; Mora, Cristina; Fedele, Stefania; Invernizzi, Roberto William; Gennarelli, Massimo; Piovani, Giovanna; Kunath, Tilo; Millan, Mark J.; Merlo Pich, Emilio; Spano, PierFranco
Abstract : The antiparkinsonian ropinirole and pramipexole are D3 receptor- (D3R-) preferring dopaminergic (DA) agonists used as adjunctive therapeutics for the treatment resistant depression (TRD). While the exact antidepressant mechanism of action remains uncertain, a role for D3R in the restoration of impaired neuroplasticity occurring in TRD has been proposed. Since D3R agonists are highly expressed on DA neurons in humans, we studied the effect of ropinirole and pramipexole on structural plasticity using a translational model of human-inducible pluripotent stem cells (hiPSCs). Two hiPSC clones from healthy donors were differentiated into midbrain DA neurons. Ropinirole and pramipexole produced dose-dependent increases of dendritic arborization and soma size after 3 days of culture, effects antagonized by the selective D3R antagonists SB277011-A and S33084 and by the mTOR pathway kinase inhibitors LY294002 and rapamycin. All treatments were also effective in attenuating the D3R-dependent increase of p70S6-kinase phosphorylation. Immunoneutralisation of BDNF, inhibition of TrkB receptors, and blockade of MEK-ERK signaling likewise prevented ropinirole-induced structural plasticity, suggesting a critical interaction between BDNF and D3R signaling pathways. The highly similar profiles of data acquired with DA neurons derived from two hiPSC clones underpin their reliability for characterization of pharmacological agents acting via dopaminergic mechanisms.